The Greek Theatre in Pontos, Russia and the Soviet Union - Fotiadis, Konstantinos (Études helléniques / Hellenic Studies, 2008)
Despite its outstanding significance for all of Hellenism, the Greek Theatre of Pontos, Russia and the former Soviet Union still remains almost totally unknown, even to those who are interested in and promote ecumenical Hellenism. This article aims at fulfilling this need by reflecting on the diachronic contribution of Hellenism in these most sensitive and historically critical regions which, like Pontos and Russia, played an important role even in the Greek uprising of 1821. The author analytically examines the vicissitudes which Greek theatre activities, since their inception in Pontos after 1860, in Russia after the founding of the Filiki Etaireia in Odessa and in the USSR after the Bolshevik rise to dominance in the early 1900s, have faced in these regions under the geo-political, cultural and linguistic adversities created by the various local regimes.